Toruń University Ethnology in Relation to Museology Education - Wojciech Olszewski (Zbiór Wiadomości do Antropologii Muzealnej, 2023)
The initiator of Toruń university ethnology and the person who shaped its profile for many years was Professor Maria Znamierowska-Prüfferowa. She came to Toruń from Vilnius, where the ethnographic museum was part of Stefan Batory University. She also brought with her the idea of Prof. Cezaria Baudouin de Courtenay-Ehrenkreutz, which emphasised the crucial role of museum experience in the education of ethnology students. This idea has been consistently present in the study programmes offered by the Department of Ethnology and Cultural Anthropology at Nicolaus Copernicus University in Toruń. These programmes are implemented in constant collaboration with Maria Znamierowska-Prüfferowa Ethnographic Museum in Toruń, the Museum of the Mazovian Countryside in Sierpc, and several other institutions. Graduates of the Toruń university work in ethnographic museums across Poland, often holding managerial positions, and collaborate with the Department in teaching museology to successive generations of students.